2009
DOI: 10.1638/2008-0154.1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Evaluation of Clinically Healthy Captive Maned Wolves (Chrysocyon brachyurus)

Abstract: The objective of this project was to determine radiographic vertebral heart sizes and electrocardiographic (ECG) and echocardiographic measurements in healthy anesthetized maned wolves (Chrysocyon brachyurus). The wolves, housed at the White Oak Conservation and Smithsonian National Zoo Conservation and Research Centers, were being anesthetized for annual examinations. Cardiac auscultation, thoracic radiographs, a standard 6-lead ECG, and echocardiography were performed on the wolves while they were under gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
7
11
2
5
Order By: Relevance
“…The PR and QT intervals are considered inversely proportional to heart rate (Tilley 1992) and may be elevated in anesthetized animals as observed by Szabuniewicz et al (1978) in capybaras, due to the positive Chrono-tropic effect of dissociative anesthetics described by Souza et al (2002) in dogs. The QRS complex duration values obtained in this study were similar to normal values of Brazilian agouti, capybaras, cheetahs, leopards and maned wolves (Szabuniew et al 1978, Schumacher et al 2003, Estrada et al 2009, Oda et al 2009, Diniz et al 2013) and higher than those reported in small rodents (Szabuniew et al 1971, Dudás-Györki et al 2011) and dogs (Tilley 1992). Although the variation in these values may not be correlated with size or heart rate in these animals, the value obtained is considered normal when compared with other species.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The PR and QT intervals are considered inversely proportional to heart rate (Tilley 1992) and may be elevated in anesthetized animals as observed by Szabuniewicz et al (1978) in capybaras, due to the positive Chrono-tropic effect of dissociative anesthetics described by Souza et al (2002) in dogs. The QRS complex duration values obtained in this study were similar to normal values of Brazilian agouti, capybaras, cheetahs, leopards and maned wolves (Szabuniew et al 1978, Schumacher et al 2003, Estrada et al 2009, Oda et al 2009, Diniz et al 2013) and higher than those reported in small rodents (Szabuniew et al 1971, Dudás-Györki et al 2011) and dogs (Tilley 1992). Although the variation in these values may not be correlated with size or heart rate in these animals, the value obtained is considered normal when compared with other species.…”
Section: Discussionsupporting
confidence: 85%
“…The P wave duration, PR, and QT intervals in pacas under chemical restraint were similar to that reported for capybaras (Szabuniewicz et al 1978) and other wild mammals using a similar restraint protocol (Schumacher et al 2003, Estrada et al 2009, Oda et al 2009), but were slightly larger than in Brazilian agouti, rabbits, ferrets and dogs under physical restraint (Szabuniew et al 1971, Tilley & Goodwin 2002, Dudás Györki et al 2011, Diniz et al 2013). Nevertheless, the P wave amplitude was similar to that found in non-anesthetized ferrets, Brazilian agouti and chemical restrained cheetahs (Schumacher et al 2003, Dudás-Györki et al 2011, Diniz et al 2013).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations